A standardised restriction fragment length polymorphism (RFLP) method for typing Mycobacterium avium isolates links IS901 with virulence for birds - Dvorska, Lenka; Bull, Tim John; Bartos, Milan; Matlova, Ludmila; Svastova, Petra; Weston, Ross Tim; Kintr, Jaromir; Parmova, Ilona; Van Soolingen, Dick; Pavlik, Ivo (Journal of microbiological methods, 2003)
A standardised method for PvuII-PstI-IS901 restriction fragment length polymorphism (RFLP) typing was developed and evaluated against 173 isolates of Mycobacterium avium subsp. avium and M. avium subsp. silvaticum originating from birds (N=46) and their aviaries (N=5), pigs (N=85), cattle (N=18), reference serotype strains (N=9), humans (N=7), a horse (N=1), a nutria (N=1), and strain M. avium subsp. avium ST 18 (formerly M. avium subsp. paratuberculosis ST 18). PvuII-IS1245 RFLP typing was also performed on all isolates. DNA was digested in parallel by restriction endonucleases PvuII or PstI and hybridised to standard probes prepared by PCR. DNA fingerprints were scanned by CCD camera and analysed by the Gel Compar (Applied Maths, Version 4.1, Kortrijk, Belgium) software using a standard isolate control profile. A total of 52 PvuII-PstI RFLP profiles was described including 25 PvuII RFLP profiles designated A to Y and 25 PstI RFLP profiles designated A1-L3. Profiles were found to be stable in vivo and in vitro after multiple subcultures. High IS901 copy number was associated with a "bird" PvuII-IS1245 RFLP profile and low IS901 copy number with M. avium subsp. avium isolates from humans and the nutria. A virulence assay of 100 IS901-positive isolates using intramuscular infections of pullets showed 83 isolates differentiated into 32 RFLP types to be virulent and 17 isolates differentiated into 12 RFLP types as nonvirulent. Attenuation of virulence for pullets could be attributed to either multiple in vitro subculture, polyclonal infection or human passage and was not related to IS901 or IS1245 profiles.
Keywords: Virulence; polymorfismus délky restrikčních fragmentů; Bacterial Typing Techniques; ptáci; Birds; Animals; transpozibilní elementy DNA; lidé; DNA Transposable Elements; Mycobacterium avium; Humans; zvířata; Polymorphism, Restriction Fragment Length; techniky typizace bakterií; virulence